Associations Between Jet Lag and Cortisol Diurnal Rhythms After Domestic Travel - Doane, Leah D. (2010)
OBJECTIVE: Millions of adults in the United States travel abruptly across time zones each year. Nevertheless, the impact of traveling over relatively short distances (across 3 or fewer time zones) on diurnal patterning of typical physiological response patterns has yet to be studied in a large, epidemiological sample. DESIGN: The current research focuses on 764 middle-aged men comparing variations in diurnal cortisol regulation based on number of time zones traveled eastward or westward the day before. MAIN OUTCOME MEASURE: Participants provided samples of salivary cortisol at waking, 30-min postwaking, 10 a.m., 3 p.m., and bedtime. RESULTS: Eastward travel was associated with a steeper salivary cortisol awakening response ( p < .01) and lower peak (PEAK) levels of salivary cortisol the next morning ( p < .05). Westward travel was associated with lower peak levels of cortisol the next morning ( p < .05). Effect sizes for these differences ranged from Cohen’s d = .29 to .47. Differences were not present for 2 days in their home environment. CONCLUSIONS: The results provide evidence that traveling across time zones is associated with diurnal cortisol regulation and should be studied further to understand the subsequent impacts on health and well-being in large national samples.